2018
DOI: 10.1038/s41375-018-0051-y
|View full text |Cite
|
Sign up to set email alerts
|

Universal genetic testing for inherited susceptibility in children and adults with myelodysplastic syndrome and acute myeloid leukemia: are we there yet?

Abstract: Comprehensive genomic profiling of myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML) cases have enabled the detection and differentiation of driver and subclonal mutations, informed risk prognostication, and defined targeted therapies. These insights into disease biology, and management have made multigene-acquired mutation testing a critical part of the diagnostic assessment of patients with sporadic MDS and AML. More recently, our understanding of the role of an increasing number of inherited g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 47 publications
0
43
0
2
Order By: Relevance
“…e identi cation of some genes involved in inheritance of hematological malignancies allowed to recognition of an independent entity in last revision of WHO classi cation and also represents a further step toward the precision and personalized therapy [15,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…e identi cation of some genes involved in inheritance of hematological malignancies allowed to recognition of an independent entity in last revision of WHO classi cation and also represents a further step toward the precision and personalized therapy [15,24].…”
Section: Discussionmentioning
confidence: 99%
“…e implication of some of them in the pathogenesis of genetic predisposition to neoplasia is still a matter of debate. Recent evidences highlighted the importance of sequencing by NGS in these patients and also of investigating the regulatory and intragenic portions instead of the only coding regions which are conventionally queried [17,24]. is approach is still mandatory for the study of ANKRD26 since the known mutations associated with MDS/ AML pedigrees a ect the 5′UTR of the gene [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall prevalence of predisposing germline mutations is not well established, but multiple studies have shown that 4%‐13% of pediatric/young adults and 5% of adult MDS/AML patients are carriers of inherited cancer susceptibility mutations . However, the contribution of hereditary cases is most likely underestimated, especially those in which the inherited genetic lesion is associated with diseases diagnosed later in life.…”
Section: Introductionmentioning
confidence: 99%
“…3 The overall prevalence of predisposing germline mutations is not well established, but multiple studies have shown that 4%-13% of pediatric/young adults and 5% of adult MDS/AML patients are carriers of inherited cancer susceptibility mutations. 4 However, the contribution of hereditary cases is most likely underestimated, especially those in which the inherited genetic lesion is associated with diseases diagnosed later in life. Over the last two decades, genomic sequencing efforts of individuals belonging to families with a history of hematological malignancies have revealed several new susceptibility loci, including CEBPA, 5 GATA2, 6 ETV6, 7 DDX41, 8 RUNX1, 9 ANKRD26, 10 and SRP72.…”
Section: Introductionmentioning
confidence: 99%